Azure App Service Web Apps Configuring and Troubleshooting LiveLessons Video - Cheshire, Jim (Sams, 2017)
Duration 8 Hours Overview Learn from an expert while you become the expert. Whether you're a beginner or an advanced user, you'll find plenty to learn about configuring and troubleshooting a Web App running on the popular Azure App Service platform. Description Azure App Service is a popular and fast- changing technology that makes it easy to start a website in minutes. After you've created your site, you'll want to explore more advanced features like SSL certificates, custom domain names, using Docker containers, authentication, deployment slots, hybrid connections, and more. You might also encounter problems such as errors, a slow website, or slow pages. In this course, you learn how to deal with all of these configuration and troubleshooting scenarios, and by the end of the course you'll be an expert in Web Apps running on Azure App Service. Skill Level All Levels What You Will Learn * Creating Web Apps in Azure App Service on Windows and Linux * Deploying Web Apps to Azure App Service * Configuring Web Apps * SSL * Custom domain names * Traffic routing * Traffic manager * Authentication and authorization * Docker containers * Hybrid connections * Backing up and cloning Web Apps * Using deployment slots * Scaling up and scaling out * Monitoring Web Apps and setting alerts * Troubleshooting error messages * Troubleshooting slow performance Who Should Take This Course Anyone who would like to take advantage of the speed and power of a website running on Web Apps in Azure App Service. From people with little to no experience to advanced users who need to dig in to complex problems, this course offers something for everyone. Course Requirements None, other than an Azure subscription About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world- leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Prentice Hall, Sams, and Que Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.